Hydrogen-rich water protects against acetaminophen-induced hepatotoxicity in mice - Zhang, Jing-Yao (World J Gastroenterol, 2015)
AIM: To investigate the hepatoprotective effects and mechanisms of hydrogen-rich water (HRW) in acetaminophen (APAP)-induced liver injury in mice. METHODS: Male mice were randomly divided into the following four groups: normal saline (NS) control group, mice received equivalent volumes of NS intraperitoneally (ip); HRW control group, mice were given HRW (same volume as the NS group); APAP + NS group, mice received NS ip for 3 d (5 mL/kg body weight, twice a day at 8 am and 5 pm) after APAP injection; APAP + HRW group, mice received HRW for 3 d (same as NS treatment) after APAP challenge. In the first experiment, mice were injected ip with a lethal dose of 750 mg/kg APAP to determine the 5-d survival rates. In the second experiment, mice were injected ip with a sub-lethal dose of 500 mg/kg. Blood and liver samples were collected at 24, 48, and 72 h after APAP injection to determine the degree of liver injury. RESULTS: Treatment with HRW resulted in a significant increase in the 5-d survival rate compared with the APAP + NS treatment group (60% vs 26.67%, P < 0.05). HRW could significantly decrease the serum alanine aminotransferase level (24 h: 4442 ± 714.3 U/L vs 6909 ± 304.8 U/L, P < 0.01; 48 h: 3782 ± 557.5 U/L vs 5111 ± 404 U/L, P < 0.01; and 3255 ± 337.4 U/L vs 3814 ± 250.2 U/L, P < 0.05, respectively) and aspartate aminotransferase level (24 h: 4683 ± 443.4 U/L vs 5307 ± 408.4 U/L, P < 0.05; 48 h: 3392 ± 377.6 U/L vs 4458 ± 423.6 U/L, P < 0.01; and 3354 ± 399.4 U/L vs 3778 ± 358 U/L, respectively) compared with the APAP treatment group. The alkaline phosphatase, total bilirubin and lactate dehydrogenase levels had the same result. Seventy-two hours after APAP administration, liver samples were collected for pathological examination and serum was collected to detect the cytokine levels. The liver index (5.16% ± 0.26% vs 5.88% ± 0.073%, P < 0.05) and percentage of liver necrosis area (27.73% ± 0.58% vs 36.87% ± 0.49%, P < 0.01) were significantly lower in the HRW-treated animals. The malonyldialdehyde (MDA) contents were significantly reduced in the HRW pretreatment group, but they were increased in the APAP-treated group (10.44 ± 1.339 nmol/mg protein vs 16.70 ± 1.646 nmol/mg protein, P < 0.05). A decrease in superoxide dismutase (SOD) activity in the APAP treatment group and an increase of SOD in the HRW treatment group were also detected (9.74 ± 0.46 U/mg protein vs 12.1 ± 0.67 U/mg protein, P < 0.05). Furthermore, HRW could significantly increase the glutathione (GSH) contents (878.7 ± 76.73 mg/g protein vs 499.2 ± 48.87 mg/g protein) compared with the APAP treatment group. Meanwhile, HRW could reduce the inflammation level (serum TNF-α: 399.3 ± 45.50 pg/L vs 542.8 ± 22.38 pg/L, P < 0.05; and serum IL-6: 1056 ± 77.01 pg/L vs 1565 ± 42.11 pg/L, P < 0.01, respectively). In addition, HRW could inhibit 4-HNE, nitrotyrosine formation, JNK phosphorylation, connexin 32 and cytochrome P4502E expression. Simultaneously, HRW could facilitate hepatocyte mitosis to promote liver regeneration. CONCLUSION: HRW has significant therapeutic potential in APAP-induced hepatotoxicity by inhibiting oxidative stress and inflammation and promoting liver regeneration.